Indications and Contraindications to Reconstructive Surgery in Ulcerative Colitis - David Johnston (Canadian Journal of Gastroenterology)
Surgical treatment is often needed for patients with ulcerative colitis because of toxic dilation, intractability or risk of cancer. Precise diagnosis is vital to exclude Crohn's disease and infective colitis, although patients with `indeterminate' colitis often do well after reconstructive surgery. Restorative proctocolectomy, in which the anal sphincter is preserved and a pelvic ileal reservoir is used as a substitute for the rectum, is the standard surgical procedure, supplanting panproctocolectomy with ileostomy. Ileorectal anastomosis should also be considered, but is only suitable for patients with relative rectal sparing, and meticulous sigmoidoscopic follow-up is essential. For toxic dilation, colectomy with ileostomy and mucous fistula is recommended, proctectomy and reconstruction being deferred until the patient is fitter. For most patients, the entire colon and rectum are removed and a pelvic ileal reservoir is anastomosed to the anus. Many types of reservoir have been proposed, but randomized trials are few, and it seems that the J pouch is as good as the S or W pouches, and technically is simpler. The operative mortality of restorative proctocolectomy worldwide has been about 1%, thanks largely to the routine use of a temporary defunctioning ileostomy. A one-stage procedure without ileostomy is permissible if the patient is relatively fit and the surgeon is in attendance for 10 days after operation, but omission of the ileostomy certainly increases the risk to life and the postoperative morbidity, and should thus not be done in debilitated patients or in those on high dose steroids. Resection of the mucosal lining of the anal canal above the dentate line (`mucosal proctectomy') was formerly routine, but leads to diminished sphincter pressure and sensation, such that preservation of the entire motor and sensory sphincteric complex is now advocated by many authors. Omission of mucosal stripping renders the procedure technically simpler and quicker, and is associated with better sphincter function, with less fecal leakage. However, a small rim of inflamed mucosa may then be left above the anal transitional zone which theoretically could lead to risk of recurrent inflammation or even predispose to malignant change.